2023
DOI: 10.1039/d3cy00637a
|View full text |Cite
|
Sign up to set email alerts
|

Large Au@Pd/PdOx core–porous shell nanoparticles as efficient ethanol oxidation electrocatalysts

Abstract: In this article, large Au@Pd core-porous shell nanoparticles (NPs) with diameters of between 20 and 60 nm were synthesized by the seed-mediated growth method. Cetyltrimethylammonium chloride, used as a surfactant...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
2
1
0
Order By: Relevance
“…The previous literature investigated that the formation of ultrathin layer PdO and PdO/PdO 2 on the Pd metal surface significantly enhances EOR activity in alkali medium. ,, Krittayavathanum et al reported that the deposition of the thin PdO layer on Pd easily binds ethanol and its intermediates, leading to high current density, and the decline in current density with increasing cycling is due to the higher amount of PdO deposition on the Pd surface, activity similar to that of the bulk PdO . Therefore, our observations agree well with the previous results. ,, …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The previous literature investigated that the formation of ultrathin layer PdO and PdO/PdO 2 on the Pd metal surface significantly enhances EOR activity in alkali medium. ,, Krittayavathanum et al reported that the deposition of the thin PdO layer on Pd easily binds ethanol and its intermediates, leading to high current density, and the decline in current density with increasing cycling is due to the higher amount of PdO deposition on the Pd surface, activity similar to that of the bulk PdO . Therefore, our observations agree well with the previous results. ,, …”
Section: Resultssupporting
confidence: 91%
“…This infers that CuO favors the formation of PdO and oxygen released by the PdO-to-Pd conversion can oxidize ethanol, and this might be the reason for the initial growth of current density. ,, The small reduction of current density after 500 cycles of CV in visible light is due to the deactivation and poisoning of the catalyst surface. The previous literature investigated that the formation of ultrathin layer PdO and PdO/PdO 2 on the Pd metal surface significantly enhances EOR activity in alkali medium. ,, Krittayavathanum et al reported that the deposition of the thin PdO layer on Pd easily binds ethanol and its intermediates, leading to high current density, and the decline in current density with increasing cycling is due to the higher amount of PdO deposition on the Pd surface, activity similar to that of the bulk PdO . Therefore, our observations agree well with the previous results. ,, …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation